An update on available pain medications - Elzbieta Osuch; Andre Marais (South African Family Practice)
Pain is a complex interaction of sensory, emotional and behavioural factors. Chronic pain is among the most common reasons for seeking medical attention. In contrast to acute pain, where the goal is primary pain relief, the effective management of chronic pain is complex and not fully understood. Multimodal pain therapy is often required to treat chronic or persistent pain syndromes. These include pharmacological agents, physical interventions, behavioural changes and surgical approaches. Pharmacological interventions are the most widely used therapeutic options to treat acute and persistent pain.